The end of poverty : economic possibilities for our time - Sachs, Jeffrey D. (New York : Penguin Press, 2005)
"Hailed by Time as one of the world's 100 Most Influential People, Jeffrey Sachs is world renowned for his work around the globe advising economies in crisis. He has advised a broad range of world leaders and international institutions on the challenges of hyperinflation, disease, post-communist transition, and extreme poverty. Now, at last, he draws on all he has learned from twenty-five years of work to offer a uniquely informed vision of the keys to economic success in the world today and the steps that are necessary to achieve prosperity for all.
Contents. One. A global family portrait. -- Two. The spread of economic prosperity. -- Three. Why some countries fail to thrive. -- Four. Clinical economics. -- Five. Bolivia's high-altitude hyperinflation. -- Six. Poland's return to Europe. -- Seven. Reaping. -- The whirlwind : Russia's struggle for normalcy. -- Eight. China : catching up after half a millennium. -- Nine. India's market reforms : the triumph of hope over fear. -- Ten. The voiceless dying : Africa and disease. -- Eleven. The millennium , 9/11, and the United Nations. -- Twelve. On-the-ground solutions for ending poverty. -- Thirteen. Making the investments needed to end poverty. -- Fourteen. A global compact to end poverty. -- Fifteen. -- Can the rich afford to help the poor?. -- Sixteen. Mythsand magic bullets. -- Seventeen. Our generation's challenge. -- Eighteen. Our generation's challenge.
Includes bibliographical references (p. 369-384) and index.
Keywords: ASISTENCIA ECONOMICA -- PAISES EN DESARROLLO; CRECIMIENTO ECONOMICO -- PAISES EN DESARROLLO; PAISES EN DESARROLLO -- CONDICIONES ECONOMICAS; PAISES EN DESARROLLO -- POLITICA ECONOMICA